CONSTRUCTION PLANNING OF THE UPPER STRUCTURE OF THE PKP-PK BUILDING AT HUSEIN SASTRANEGARA AIRPORT BANDUNG - Ramadhan Hasibuan, Syahumi; Wasito, Bambang; Meilawati Eka Putri, Karina (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The PKP-PK building is one of the facilities located at an airport to visually monitor aircraft movements. In connection with this, at Husein Sastranegara Airport Bandung there is a PKP-PK building. In this study, it is intended to plan the PKP-PK building structure in accordance with SNI. so that in analyzing the structure, the SRPMK (Special Moment Bearing Frame System) method is used. In the calculation of the structure used SRPMK (Special Moment Bearing Frame System) and Strong Column Weak Beam which refers to SNI 1726: 2019 concerning earthquakes. In planning the building structure, SNI 2847: 2019 concerning reinforced concrete and SNI 1727: 2018 for loading are used. In this research, the SAP 2000 auxiliary program is used for 3D building modeling, PCAColumn for column interaction diagram calculation, and Autocad 2018 for reinforcement details. In the planning, 400/600mm main beam, with 5 D 19 flexural reinforcement at positive moment, at 7 D 19 flexural reinforcement at negative moment, 300/500mm sub-beam, with 3 D 16 flexural reinforcement at positive moment, at 5 D 16 flexural reinforcement at negative moment, 200/300 sub-beam with 3 D 13 flexural reinforcement at positive moment, at 5 D 13 flexural reinforcement at negative moment 600/600 column and 100 mm plate thickness and structural reinforcement details are included in the engineering drawings. In addition, the PKP-PK structural design control check based on SNI 1726: 2019 has met the requirements and fulfills the Strong Column Weak Beam concept and the cost required for the PKP-PK building construction planning is Rp1,324,860,000.00 (One Billion Three Hundred Twenty Four Million Eight Hundred Sixty Thousand Rupiah).